Museo Federico II Stupor Mundi. Palazzo Ghislieri.: Piazza Federico II, 3, 60035 Jesi (AN) - Dubbini, Rachele (Ex Novo: Journal of Archaeology, 2017)
In July 2017 opened in Jesi (Ancona, Italy) an “experience museum” dedicated to the figure of the imperator Frederick II. According to tradition, indeed, Frederick II was born in the city center of Jesi: here his mother decided to give birth to the royal son, in a tent placed in the middle of the public square. This expedient was necessary to prove the royal lineage of the new born. Based on this famous tale, the city of Jesi has seen in Frederick II an icon of the local cultural identity since the Middle Age. Yet the collective memory seemed not strong enough to remember to the inhabitants so as to the tourists, who crowd into the region during summer, the importance of such historical figure. For this reason, a local entrepreneur decided to invest in the creation of a museum on Frederick II, which could properly present life and deeds of the imperator, even if in Jesi there was no material traces of his passage, but only the memory of the royal tent. The museum has an innovative approach, especially as concerns the communication of the historical value of the imperator, having been designed as an “immersive and multisensorial trip” across the life of Frederick II. Moreover, it is also a pioneering undertaking - in comparison to most Italian museums - since it has been conceived as a “cultural enterprise”, having as one of its main aim the social and economic development of the local territory. The massive presence of private investors has probably influenced such a choice and the result is an interesting experiment that does live up to the visitors’ expectations.